Islamization and Social Transformation in Colonial Manna, Bencoolen (1824-1942) - Irama, Dedi; Herawati, Emy (Islamica: Jurnal Studi Keislaman, 2025)
This article examines the process of Islamization and its impact on the socio-economic transformation of the community in Onderafdeeling Manna, Bencoolen or Bengkulu Residency, during the Dutch colonial period, spanning from 1824 to 1942. The primary objective of this study is to identify the early figures who disseminated Islam in the region and analyse how Islamic teachings influenced the lifestyle of the local community. Using historical methods through the stages of heuristics, source criticism, interpretation, and historiography, this study finds that Islam entered the Manna region around the 1880s through the preaching of Shaykh Muhammad Amin from Nias Island. Islamic activities developed through the establishment of large mosques, such as Al-Manar, the formation of Islamic organisations like Muhammadiyah and Nahdlatul Ulama, and the growth of Sufi orders in the post-independence period. This process also encouraged changes in the community’s economic behaviour, primarily through shifts in trade ethics, increased cooperation in agriculture, and the development of waqf and zakāh-based initiatives. These findings demonstrate that Islam serves not only as a religion but also as a social and cultural force capable of transforming society’s structure in a peaceful and sustainable manner.